Axial motor clues to identify atypical parkinsonism: A multicentre European cohort study - Borm, Carlijn D J M; Krismer, Florian; Wenning, Gregor K; Seppi, Klaus; Poewe, Werner; Pellecchia, Maria Teresa; Barone, Paolo; Johnsen, Erik L; Østergaard, Karen; Gurevich, Tanya; Djaldetti, Ruth; Sambati, Luisa; et al. (Parkinsonism & related disorders, 2018)
OBJECTIVE: Differentiating Parkinson's disease (PD) from atypical parkinsonian disorders (APD) such as Multiple System Atrophy, parkinsonian type (MSA-p) or Progressive Supranuclear Palsy (PSP-RS) can be challenging. Early signs of postural Instability and gait disability (PIGD) are considered clues that may signal presence of APD. However, it remains unknown which PIGD test - or combination of tests - can best distinguish PD from APD. We evaluated the discriminative value of several widely-used PIGD tests, and aimed to develop a short PIGD evaluation that can discriminate parkinsonian disorders. METHODS: In this multicentre cohort study patients were recruited by 11 European MSA Study sites. Patients were diagnosed using standardized criteria. Postural instability and gait disability was evaluated using interviews and several clinical tests. RESULTS: Nineteen PD, 21 MSA-p and 25 PSP-RS patients were recruited. PIGD was more common in APD compared to PD. There was no significant difference in axial symptoms between PSP-RS and MSA-p, except for self-reported falls (more frequent in PSP-RS patients). The test with the greatest discriminative power to distinguish APD from PD was the ability to perform tandem gait (AUC 0.83; 95% CI 71-94; p < 0.001), followed by the retropulsion test (AUC 0.8; 95% CI 0.69-0.91; p < 0.001) and timed-up-and-go test (TUG) (AUC 0.77; 95% CI 0.64-0.9; p = 0.001). The combination of these three tests yielded highest diagnostic accuracy (AUC 0.96; 95% CI 0.92-1.0; p < 0.001). CONCLUSIONS: Our study suggests that simple "bedside" PIGD tests - particularly the combination of tandem gait performance, TUG and retropulsion test - can discriminate APD from PD.
Keywords: Female; lidé středního věku; kohortové studie; mužské pohlaví; senioři nad 80 let; Parkinsonian Disorders; prospektivní studie; Humans; Europe; dospělí; neurologické poruchy chůze; Prospective Studies; Parkinson Disease; Postural Balance; Gait Disorders, Neurologic; Evropa; lidé; Middle Aged; Diagnosis, Differential; Cohort Studies; Aged, 80 and over; senioři; posturální rovnováha; diferenciální diagnóza; Parkinsonova nemoc; ženské pohlaví; Aged; Adult; parkinsonské poruchy; Male